The manifestation of global seismic activity in variations of the intensity of on-radiation in a seismically quiet region - Захаров, И. Г.; Тырнов, О. Ф. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
Variations of VLF emission in the near-Earth atmosphere during periods of sharp change in global seismic activity are considered according to daily data for 2007-2008 in a seismically quiet area in Kharkiv province, Ukraine 49.7 °N; 36.2 °E. Effects of global seismic activity in the variations of VLF emission in seismically quiet region, including before of activity increase, is established. The important role of background seismicity in these processes is shown. The features of VLF emission variation depending on the earthquake magnitude аnd possible physical mechanisms of the phenomenon are considered. An important role in the response of VLF emission to remote earthquakes can be played by such a nonlinear phenomenon as spontaneous electromagnetic emission of the Earth, the generation and propagation of which is due to the continuous emanation of deep fluids.